PENYAJIAN PENDAPATAN KOMPREHENSIF LAIN: INVESTIGASI PADA INDUSTRI INFRASTRUKTUR DAN UTILITAS - Sidantha, Bagus; Ahmar, Nurmala; Mulyadi, JMV (Universitas Pakuan, 2016)
The purpose of this study was to investigate how the implementation of the presentation of other comprehensive income (OCI) after IFRS implementation in the industrial sector of infrastructure and utility that is listed in the Indonesia Stock Exchange in 2012-2015. The samples were processed as many as 48 companies. OCI component is observed on foreign exchange IAS 10, IAS 24, employee benefits, IAS 55 available for sale and cash flow hedges, IAS 16/19 revaluation of tangible and intangible, and SFAS 15 associations and venture. These research data analysis methods were using cross tabulation and analysis done by testing different test Cramers V because the data being tested were nominal and non-parametric. Results of the study were that the foreign exchange component of OCI, employment benefits and securities available for sale were the components most often served. As for the foreign exchange component was found a difference in the presentation. Research on the future OCI can be done by digging a further impact on the condition value of OCI micro and macro enterprises.Â Keywords: Other Comprehensive Income, Foreign Exchange, Employee Benefits, Securities Available for Sale and Hedging, Revaluation of Tangible and Intangible, and Association